Effect of folate supplementation on hematological profile of sickled children: A longitudinal study - Panda, Prakash Chandra; Mishra, Nihar Ranjan; Pradhan, Arpita; Pattanayak, Durgadatta; Nayak, Bijan Kumar; Khatua, Amlan (Indian Journal of Child Health, 2020)
Background: Folic acid supplementation in sickle cell (SC) children has been a topic of interest for the past two decades. Objective: The objective of the study was to determine the changes in the hematological profile of cohorts of SC children after receiving folic acid tablets 1 mg/day. Materials and Methods: A total of 425 homozygous SC were enrolled in this present prospective study as per predefined inclusion and exclusion criteria, after receiving written informed consent from the parents/guardians. Patients were followed up at four subsequent visits (0, 6, 12, and 24 weeks). All the relevant statistics were done by SPSS v25.0. Results: Out of 425 subjects, 246 (57.9%) were male and 179 (42.1%) were female with a mean age of the study population being 7.09 (3.58) years. There was no significant change in the mean sickle hemoglobin, fetal hemoglobin, hemoglobin, corrected reticulocyte count, total leukocyte count, total platelet count, absolute neutrophil and lymphocyte count, mean corpuscular volume, mean corpuscular hemoglobin (MCH), and MCH concentration over a period of 24 weeks (p>0.05); however, there was a significant increase in the mean serum folate level (p